Tannin-based Polyurethane Coating for Quality Improvement of Roof Tiles Composite - Aprilia Kartikawati; Sarah Augustina; Muhammad Adly Rahandi Lubis; Sukma Surya Kusumah; Adi Santoso; Jajang Sutiawan; Deni Zulfiana; Harisyah Manurung; Evalina Herawati; Marwanto Marwanto; Hasan Ashari Oramahi; Manggar Arum Aristri; et al. (BioResources, 2025)
Roof tiles come in various forms and are crucial to residential construction. A roof tile composite offers the market a selection of superior roof tile products in terms of strength, low density, and environmental friendliness. This research aimed to improve the surface performance and durability of sorghum bagasse-based roof tile composite (SBRTC) through surface coating with natural polymer. Sorghum bagasse was made into roof tile composite using a mixture of molasses and citric acid adhesives (50:50) with a target density of 0.6 g/cm3. Furthermore, the SBRTC surface was coated with tannin–polyurethane at different concentrations (10%, 20%, and 30%), and the results were compared with both uncoated and polyurethane-coated samples. The parameters tested included physical and mechanical properties, surface characteristics, and durability against termite and brown-rot fungi. The result showed increasing density, dimensional stability, mechanical properties, and durability. At the same time, the moisture content decreased. Surface performance exhibits a decrease in the average surface roughness (Ra) value, indicating a smoother surface of roof tile composite after surface coating. Furthermore, a high contact angle, low K-value, and low wettability were achieved. It indicates a more hydrophobic surface. The optimal tannin concentration in the coating solution was 20%.